Deliberation and Action on Participatory Governance in Integrated Disaster Management in Kotamobagu - Asriyanti, ‎ (KnE Social Sciences, 2025)
Disasters can result in property losses, environmental damage, casualties, and psychological impacts. Disaster management, which includes a number of handling tasks before, during, and after a disaster, is a component of national development. The purpose of this research is to analyze deliberation and action in participatory governance in integrated disaster management in Kotamobagu. The research used in this study is a qualitative approach. Data were collected through in-depth interviews, field observation data, and documents. Data sources consist of primary data and secondary data, while data analysis is carried out using interactive methods. The informants in this research are the local and central government, disaster management agencies and institutions, TNI and Polri, local communities, academic and research parties, private sector, international organizations, media, extension, and educators. The results showed that integrated natural disaster management in Kotamobagu has not been implemented effectively. The deliberation element indicates that there is a lack of public understanding about the importance of mitigation, as well as limited resources that result in the community not having adequate access to be involved in disaster management. The action element shows findings where the lack of coordination between stakeholders involved, and they tend to work partially or act individually. Therefore, coordination and synergy between stakeholders are needed. So that integrated disaster management is carried out effectively.